Making prepublication independent replication mainstream. (27th July 2018) - Tierney, Warren; Schweinsberg, Martin; Uhlmann, Eric Luis
Abstract: The widespread replication of research findings in independent laboratories prior to publication is suggested as a complement to traditional replication approaches. The pre-publication independent replication approach further addresses three key concerns from replication skeptics by systematically taking context into account, reducing reputational costs for original authors and replicators, and increasing the theoretical value of failed replications.